2007
DOI: 10.4141/p05-212
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutrient response of flax and durum wheat to phosphorus and zinc fertilizers

Abstract: . 2007. Growth and nutrient response of flax and durum wheat to phosphorus and zinc fertilizers. Can. J. Plant Sci. 87: 461-470. Flax (Linum usitatissimum L.) and durum wheat (Triticum turgidum L.) are important agricultural crops that enter the human food chain. Effective nutrient management considering nutrient interactions is important in order to increase crop yield and improve crop nutrient concentration. The objective of this study was to investigate the effect of P and Zn fertilizers on the yield and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…Moraghan (1993) reported that, in a greenhouse study with a calcareous soil, applying ZnSO 4 at 8 mg Zn/kg soil advanced the appearance of mature bolls by 15 d and increased the yield of flax seed by 33%. A similar result was reported by Jiao et al (2007), who found that applying of 10 and 20 mg Zn/kg soil in the form of ZnSO 4 enhanced the growth of flax, increased its height, and caused it to mature from 3 to 5 d earlier. Nofal et al (2011), working with a foliar Zn application, also observed that increasing the application rate also caused significant increases for growth, fiber yield and other qualities such fiber length.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Moraghan (1993) reported that, in a greenhouse study with a calcareous soil, applying ZnSO 4 at 8 mg Zn/kg soil advanced the appearance of mature bolls by 15 d and increased the yield of flax seed by 33%. A similar result was reported by Jiao et al (2007), who found that applying of 10 and 20 mg Zn/kg soil in the form of ZnSO 4 enhanced the growth of flax, increased its height, and caused it to mature from 3 to 5 d earlier. Nofal et al (2011), working with a foliar Zn application, also observed that increasing the application rate also caused significant increases for growth, fiber yield and other qualities such fiber length.…”
supporting
confidence: 88%
“…Fertilizer management may offer a cost-effective way of meeting crop requirements since appropriate fertilizer management can optimize both crop yield and crop micronutrient content (Chandi & Takkar, 1982;Jiao et al, 2007). More information is therefore needed to determine how Zn fertilizers influence both crop yield and crop micronutrient concentrations, and also the mechanical properties of plants such as flax (Alvarez, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flax is a plant that is very susceptible to Zn deficiency, particularly at low soil temperatures (Moraghan 1980). This susceptibility is heightened by P application (Burleson and Page 1967;Jiao et al 2007;Loneragan et al 1979;Millikan et al 1968;Moraghan 1984;Spratt and Smid 1978) and also influenced by the presence of Fe, which determines normal chlorophyll formation and the development of green plant tissue (Lee et al 1969). Field studies have been conducted to evaluate the interactive effects of phosphate and ZnSC>4 fertilizers on different soil types and Cd uptake and their distribution in flax (Grant and Bailey 1997;Jiao et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, when P level in the soil is smaller than 10 kg ha -1 , an addition of P fertilizers usually has a positive effect on durum wheat yield on the Brown and Dark Brown soils [86,93]. In some cases, increased fertilization with monoammonium phosphate to durum wheat could reduce soil pH and enhance root proliferation [94], but may reduce grain quality [93] or modify the micronutrient profile in the durum grain [95]. There exists a complex interplay between multi-nutrient dynamics within the rhizosphere of a durum wheat crop.…”
Section: Nitrogen and Phosphorusmentioning
confidence: 99%